Blood compatibility testing in asian elephants using an indirect antiglobulin technique to improve captive breeding success - Pakkanut Bansiddhi (2018)
© 2015 Academic Journals Inc. Feto-maternal blood incompatibility causes hematological defects that can result in abortion and neonatal anemia and may lead to calf loss, including in elephants. The aim of this study was to examine blood compatibility in Asian elephants using the indirect antiglobulin technique, for use as a breeding management tool to reduce the risk of elephant fetal loss. Forty-four blood samples collected from 22 female and 22 male elephants were subjected to standard tube cross-matching tests and examined for macroscopic and microscopic agglutination reactions. The percentages of positive reactions across three female groups based on reproductive history (unmated, mated but not pregnant, parous) were 43.94, 53.03 and 45.80, respectively and did not differ (p>0.05). Moreover, all female sample showed positive reaction results at ambient and body temperatures. These results suggest blood incompatibility occurs in elephants. Thus, it could be beneficial to avoid mating between reactive blood groups.